Activation properties of trigeminal motoneurons in participants with and without bruxism - ATIŞ TEKELİ, ELİF SİBEL (AMER PHYSIOLOGICAL SOC, 2013)
In animals, sodium-and calcium-mediated persistent inward currents (PICs), which produce long-lasting periods of depolarization under conditions of low synaptic drive, can be activated in trigeminal motoneurons following the application of the monoamine serotonin. Here we examined if PICs are activated in human trigeminal motoneurons during voluntary contractions and under physiological levels of monoaminergic drive (e. g., serotonin and norepinephrine) using a paired motor unit analysis technique. We also examined if PICs activated during voluntary contractions are larger in participants who demonstrate involuntary chewing during sleep (bruxism), which is accompanied by periods of high monoaminergic drive. In control participants, during a slowly increasing and then decreasing isometric contraction, the firing rate of an earlier-recruited masseter motor unit, which served as a measure of synaptic input to a later-recruited test unit, was consistently lower during derecruitment of the test unit compared with at recruitment (Delta F = 4.6 +/- 1.5 imp/s). The Delta F, therefore, is a measure of the reduction in synaptic input needed to counteract the depolarization from the PIC to provide an indirect estimate of PIC amplitude. The range of Delta F values measured in the bruxer participants during similar voluntary contractions was the same as in controls, suggesting that abnormally high levels of monoaminergic drive are not continually present in the absence of involuntary motor activity. We also observed a consistent onion skin effect during the moderately sized contractions (<20% of maximal), whereby the firing rate of higher threshold motor units discharged at slower rates (by 4-7 imp/s) compared with motor units with relatively lower thresholds. The presence of lower firing rates in the more fatigue-prone, higher threshold trigeminal motoneurons, in addition to the activation of PICs, likely facilitates the activation of the masseter muscle during motor activities such as eating, nonnutritive chewing, clenching, and yawning.
Keywords: motoneurons; pain; sleep bruxism; plateaus; SINGLE MOTOR UNITS; FIRING-RATE MODULATION; HUMAN MASSETER MUSCLE; CHRONIC SPINAL RATS; SLEEP BRUXISM; CALCIUM CURRENTS; CORD-INJURY; GUINEA-PIG; PHYSIOLOGICAL-PROPERTIES; VOLUNTARY CONTRACTION